2013
DOI: 10.3390/toxins5112241
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RhoA,B,C by Yersinia Cytotoxic Necrotizing Factor (CNFy) Induces Apoptosis in LNCaP Prostate Cancer Cells

Abstract: Prostate cancer is the most common malignancy, accounting for about 25% of all incident cases among men in industrialized countries. The human androgen-dependent prostate cancer cell line LNCaP, which is derived from a metastatic lesion of human prostatic adenocarcinoma, is frequently used to study prostate cancer associated signaling pathways in vitro. Recently it was described that Rho GTPase activation in these cells leads to apoptotic responses. We used the bacterial toxins CNFy and CNF1, which specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(25 reference statements)
1
16
0
Order By: Relevance
“…Therefore, it is interesting to investigate the effect that CNF1 can exert on the main events of tumor development. Two crucial aspects of that process are represented by apoptosis and the regulation of actin cytoskeleton [ 48 ]. The effect of CNF1 on apoptosis is still debated.…”
Section: Effects Of Cnf1 On Cancer Cellsmentioning
confidence: 99%
“…Therefore, it is interesting to investigate the effect that CNF1 can exert on the main events of tumor development. Two crucial aspects of that process are represented by apoptosis and the regulation of actin cytoskeleton [ 48 ]. The effect of CNF1 on apoptosis is still debated.…”
Section: Effects Of Cnf1 On Cancer Cellsmentioning
confidence: 99%
“…All data are given as mean ± SD (n ≥ 3) and significance was tested by using the Student's t-test (*P < 0.05, **P < 0.01, ***P < 0.001; ns, not significant). triggers a negative feedback mechanism resulting in blockade of the activity state of Rho (Reipschläger et al, 2012;Augspach et al, 2013). As shown by the immunoblots, this effect was apparently not caused by degradation of Rho.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, activation of Rho by PTC5 was maximal after 4 h and remained increased for at least 18 h. Interestingly, the transient effect of CNF1 was dominant in the presence of both toxins. This finding supports our previous hypothesis that CNF1‐induced activation of Rho subfamily proteins triggers a negative feedback mechanism resulting in blockade of the activity state of Rho (Reipschläger et al ., ; Augspach et al ., ). As shown by the immunoblots, this effect was apparently not caused by degradation of Rho.…”
Section: Discussionmentioning
confidence: 97%
“…For example, RhoA depletion diminishes motility, invasion [13,14], and proliferation [15] and increases apoptosis [16,17]. It has been reported that RhoA expression is an independent prognostic factor in gastric cancer, especially diffuse-type gastric cancer [18].…”
Section: Discussionmentioning
confidence: 99%